Innovative Fabrication Design for In Situ Martensite Decomposition and Enhanced Mechanical Properties in Laser Powder Bed Fused Ti6Al4V Alloy - Behzad Farhang; Ahmet Alptug Tanrikulu; Aditya Ganesh-Ram; Sadman Hafiz Durlov; Narges Shayesteh Moghaddam (Journal of Manufacturing and Materials Processing, 2023)
Ti6Al4V alloy (Ti64) is a popular material used in the aerospace, medical, and automotive industries due to its excellent mechanical properties. Laser Powder Bed Fusion (LPBF) is a promising manufacturing technique that can produce complex and net-shaped components with comparable mechanical properties to those produced using conventional manufacturing techniques. However, during LPBF, the rapid cooling of the material can limit its ductility, making it difficult to achieve high levels of ductility while maintaining the required tensile strength for critical applications. To address this challenge, this study presents a novel approach to controlling the microstructure of Ti64 during LPBF by using a border design surrounding the main parts. It is hypothesized that the design induces in situ martensitic decomposition at different levels during the fabrication process, which can enhance the ductility of the material without compromising its tensile strength. To achieve this aim, a series of Ti64 samples were fabricated using LPBF with varying border designs, including those without borders and with gaps from 0.5 to 4 mm. The microstructure, composition, and mechanical properties of the Reference sample were compared with those of the samples fabricated with the surrounding border design. It was found that the latter had a more homogenized microstructure, a higher density, and improvements in both ductility and tensile strength. Moreover, it was discovered that the level of property improvement and martensitic transformation can be controlled by adjusting the gap space between the border and the main part, providing flexibility in the fabrication process. Overall, this study presents a promising approach for enhancing the mechanical properties of Ti64 produced via LPBF, making it more suitable for critical applications in various industries.